Universal Educational Activities in Primary Grades - Abdullaev, Azimjon (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
It can be said that activities form the basis for active learning, however teachers determine which activity is effective for the development of students. One of the criteria in this determination is the student, which is the basic input of education. This article discusses universal educational activities of elementary school students as a result of a meta-subject approach that serve to deepen and expand understanding of school subjects.